The Rare Coincidence: Nonrecurrent Laryngeal Nerve Pointed by a Zuckerkandl's Tubercle - Emin Gurleyik; Sami Dogan; Omer Gunal; Mevlut Pehlivan (Case Reports in Medicine)
The safety of thyroid operations mainly depends on complete anatomical knowledge. Anatomical and embryological variations of the inferior laryngeal nerve (ILN), of the thyroid gland itself and unusual relations between ILN and the gland threaten operation security are discussed. The patient with toxic multinodular goiter is treated with total thyroidectomy. During dissection of the right lobe, the right ILN which has nonrecurrent course arising directly from cervical vagus nerve is identified and fully isolated until its laryngeal entry. At the operation, we observe bilateral Zuckerkandl's tubercles (ZTs) as posterior extension of both lateral lobes. The left ILN has usual recurrent course in the trachea-esophageal groove. The right ZT is placed between upper and middle third of the lobe points the nonrecurrent ILN. The coincidence of non-recurrent ILN pointed by a ZT is rare anatomical and embryological feature of this case. Based on anatomical and embryological variations, we suggest identification and full exposure of ILN before attempting excision of adjacent structures, like the ZT which has surgical importance for completeness of thyroidectomy.